STATUS KEBERLANJUTAN DAN FAKTOR PENGUNGKIT DIMENSI EKOLOGI DAN EKONOMI PADA PENGELOLAAN PERIKANAN TANGKAP DI KOTA TEGAL - Andi Irawan; Karyoto karyoto; Heru Kurniawan Alamsyah (Jurnal Perikanan dan Kelautan, 2022)
ABSTRACTTegal City is an area located on the North Coast of Java (Pantura) which has a strategic role in developing fishery and marine potential. In the capture fisheries sector, the City of Tegal has marine resources, human resources and adequate infrastructure. However, it is reported that the marine fishery production of Tegal City has fluctuated in the last five years. Sustainability in capture fisheries management has urgency in the life of the fishing community, the interests of the state as well as in the framework of sustainable development, including in meeting consumption needs at various levels of society. This study aims: To determine the sustainability status and leveraging factors of capture fisheries management in Tegal City on the ecological and economic dimensions. Data was collected through direct interviews with respondents through questionnaires. The data collected is data on ecological, ecological and economic aspects. This research method uses a Multi-dimensional Scaling (MDS) approach on the ecological and economic dimensions with the Rapfish technique. The Rapfish technique (Rapid Appraissal for Fisheries) is a quantitative analysis method to evaluate the sustainability of capture fisheries at the research location with attributes as required by FAO-CCRF 1995. The results of the sustainability analysis of capture fisheries management in Tegal City on the Ecological dimension of 40.25% (Less sustainable), and the Economic dimension of 54.96% (Moderately sustainable). Leverage factors on the ecological dimension include the use of illegal fishing gear with an RMS value of 3.60%, selectivity of fishing gear of 3.31% and size of fish caught 2.941%, while leverage factors in the economic dimension include ship ownership with an RMS value of 4.89%, fuel increase with an RMS value of 4.75% and the average age of fishermen with an RMS value of 4.34%. Keywords: Capture Fisheries, Sustainability, MDS, Tegal City   ABSTRAKKota Tegal merupakan daerah yang terletak di Pantai Utara Jawa (Pantura) memiliki peran strategis dalam pengembangan potensi perikanan dan kelautan. Dalam sektor perikanan tangkap, Kota Tegal memiliki sumberdaya laut, sumberdaya manusia serta infrastruktur yang memadai. Namun demikian, dilaporkan bahwa produksi perikanan laut Kota Tegal mengalami fluktuasi dalam kurun waktu lima tahun terakhir. Keberlanjutan dalam  pengelolaan perikanan tangkap memiliki urgensi dalam kehidupan masyarakat nelayan, kepentingan negara maupun dalam kerangka pembangunan berkelanjutan termasuk dalam pemenuhan kebutuhan konsumsi pada berbagai lapisan masyarakat. Penelitian ini bertujuan untuk enentukan status keberlanjutan dan atribut (factor) pengungkit pengelolaan perikanan tangkap Kota Tegal pada dimensi ekologi dan ekonomi. Pengumpulan data dilakukan melalui wawancara secara langsung dengan responden melalui kuesioner. Data yang dikumpulkan merupakan data aspek ekologi, ekologi dan ekonomi. Metode penelitian ini menggunakan pendekatan Multi-dimensional Scaling (MDS) pada dimensi ekologi dan ekonomi dengan teknik Rapfish. Teknik Rapfish (Rapid Appraissal for Fisheries) merupakan metode analisis kuantitatif untuk mengevaluasi keberlanjutan perikanan tangkap dilokasi penelitian dengan atribut sesuai dengan yang diisyaratkan FAO-CCRF 1995. Hasil analisis keberlanjutan pengelolaan perikanan tangkap di Kota Tegal pada dimensi Ekologis sebesar 40,25% (Kurang berkelanjutan),  dan dimensi Ekonomi 54,96% (Cukup berkelanjutan). Faktor pengungkit pada dimensi ekologi antara lain penggunaan alat tangkap ilegal dengan nilai RMS 3,60%, selektivitas alat tangkap 3,31% dan Ukuran Ikan tertangkap 2,941%, sedangkan factor pengungkit pada dimensi ekonomi antara lain kepemilikan kapal dengan nilai RMS 4,89%, kenaikan BBM dengan nilai RMS 4,75% dan rata-rata  usia nelayan dengan nilai RMS 4,34%. Kata kunci: Perikanan Tangkap, Keberlanjutan, MDS, Kota Tegal